Transfer of Technology - An Inevitable Risky Process to Nepal - K.C., Jagat Bahadur (Tribhuvan University Journal, 2010)
Not available. Key words: Transfer of Technology; Industrialization; Ineviatable Risky Tribhuvan University Journal Vol. XIX, 1996 Page: 149-153 Uploaded Date: 24 Nov., 2010